2022
DOI: 10.3390/s22103664
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Step Hourly Power Consumption Forecasting in a Healthcare Building with Recurrent Neural Networks and Empirical Mode Decomposition

Abstract: Short-term forecasting of electric energy consumption has become a critical issue for companies selling and buying electricity because of the fluctuating and rising trend of its price. Forecasting tools based on Artificial Intelligence have proved to provide accurate and reliable prediction, especially Neural Networks, which have been widely used and have become one of the preferred ones. In this work, two of them, Long Short-Term Memories and Gated Recurrent Units, have been used along with a preprocessing al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…To establish the parameters of each member of the CGG, one needs to equate Equation (13) to Equation ( 14) and/or Equation (15) to Equation ( 16), depending on the number of unknown parameters.…”
Section: Gini's Gamma (γ)mentioning
confidence: 99%
See 1 more Smart Citation
“…To establish the parameters of each member of the CGG, one needs to equate Equation (13) to Equation ( 14) and/or Equation (15) to Equation ( 16), depending on the number of unknown parameters.…”
Section: Gini's Gamma (γ)mentioning
confidence: 99%
“…Using MAPE, Reference [14] showed that multiple linear regression seasonality models outperformed machine learning methods in predicting daily peak loads in South Korea. A multivariate hybrid prediction model using a neural network and a pre-processing algorithm incorporating reactive consumption, humidity, and temperature was used by [15] to predict the hourly electricity consumption of a hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In order to capture the specific features of the electricity demand time series mentioned above, researchers have proposed various methods and models for the forecast of electricity demand over the past three decades [9][10][11][12][13][14][15][16][17][18][19]. Typically, these forecasting methods and models can be roughly divided into three categories: statistical methods, machine learning methods, and hybrid models.…”
Section: Introductionmentioning
confidence: 99%